2020
DOI: 10.1080/0886022x.2020.1846054
|View full text |Cite
|
Sign up to set email alerts
|

Renal allograft surveillance with allospecific T-cytotoxic memory cells

Abstract: Background Allo-antigen-specific T-cytotoxic memory cells (TcM) which express CD40 ligand (CD154) in overnight lymphocyte co-culture are strongly associated with acute cellular rejection (ACR) seen in “for cause” biopsies for renal allograft dysfunction. Specifically, when the likelihood of rejection is increased, donor-specific allospecific TcM exceed those induced by HLA-non-identical third-party cell by 1.15-fold or greater. Methods The performance of allospecific Tc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…However, the results were deemed weak due to a low sample size and a wide confidence interval. Rohan et al [ 16 ] conducted a study to assess the efficacy of allospecific CD154+ TcM in 22 individuals who received kidney transplants. Out of the 22 patients, 6 experienced TCMR and 7 showed ABMR.…”
Section: Extraction Of Rna and Clinical Markers From Histological Sam...mentioning
confidence: 99%
See 2 more Smart Citations
“…However, the results were deemed weak due to a low sample size and a wide confidence interval. Rohan et al [ 16 ] conducted a study to assess the efficacy of allospecific CD154+ TcM in 22 individuals who received kidney transplants. Out of the 22 patients, 6 experienced TCMR and 7 showed ABMR.…”
Section: Extraction Of Rna and Clinical Markers From Histological Sam...mentioning
confidence: 99%
“…The mentioned studies investigated different types of rejection in kidney-transplant recipients. A common finding among these studies was the importance of T-cell mediated rejection (TCMR) and antibody-mediated rejection (ABMR) in acute rejection [ 16 , 17 , 19 , 20 , 21 , 26 ]. Several studies identified the biomarker CD4+ CD25+/CD39+ expression to predict acute cellular rejection (ACR) as well [ 23 , 24 , 27 ].…”
Section: Extraction Of Rna and Clinical Markers From Histological Sam...mentioning
confidence: 99%
See 1 more Smart Citation
“…Resent studies showed that monitoring alloreactive memory IFN-γ-producing T cells could assess subclinical TCMR and predict de novo DSA ( 82 ), while ratio of T follicular helper cells and T follicular regulatory cells (Tfc/Tfr) was an independent risk factor for CAD ( 83 ). However, multicenter validation of its diagnostic/prognostic biomarker utility in CKTR remains to be determined ( 108 ). Both macrophages and NK cells are implicated in chronic rejection ( 21 , 109 111 ).…”
Section: Potential Biomarkers For Early Diagnosis and Prognosismentioning
confidence: 99%